∫ 0 ∞ e 2 π x − 1 x e − π x d x ∫ 0 ∞ e π 3 x − 1 3 x e − π 3 x d x = a 1 − π 4 a + 4 = a − 3 1 − π 4 2 a + 2
Find the value of a for which the above two equations hold true.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
For the first integral:
I = ∫ 0 ∞ e 2 π x − 1 x e − π x d x
Let x = π 2 u 2 , d x = π 2 2 u d u :
I = π 4 2 ∫ 0 ∞ e 2 u − 1 u 3 e − u d u
Multiplying above and below by e u :
I = π 4 2 ∫ 0 ∞ e 3 u − e u u 3 d u
Expanding in partial fractions in e u :
I = π 4 2 [ 2 1 ∫ 0 ∞ e u − 1 u 3 d u + 2 1 ∫ 0 ∞ e u + 1 u 3 d u − ∫ 0 ∞ u 3 e − u d u ]
Recall that:
∫ 0 ∞ e u − 1 u s − 1 d u = Γ ( s ) ζ ( s ) , ∫ 0 ∞ e u + 1 u s − 1 d u = Γ ( s ) η ( s ) , ∫ 0 ∞ u s − 1 e − u d u = Γ ( s ) = ( s − 1 ) !
Where ζ ( s ) is the Riemann Zeta Function , η ( s ) is the Dirichlet Eta Function and Γ ( s ) is the Gamma Function . So:
I = π 4 2 [ 2 1 ζ ( 4 ) Γ ( 4 ) + 2 1 η ( 4 ) Γ ( 4 ) − Γ ( 4 ) ]
I = π 4 2 [ 2 1 9 0 π 4 3 ! + 2 1 7 2 0 7 π 4 3 ! − 3 ! ]
I = π 4 2 [ 3 0 π 4 + 2 4 0 7 π 4 − 6 ]
I = π 4 2 [ 1 6 π 4 − 6 ]
I = 8 1 − π 4 1 2
So:
a = 8
We already have our answer, but, for the second integral, just make x = π 3 u 3 , d x = π 3 3 u 2 d u :
J = π 4 3 ∫ 0 ∞ e u − 1 u 3 e − u d u
Multiplying above and below by e u :
J = π 4 3 ∫ 0 ∞ e 2 u − e u u 3 d u
Expanding in partial fractions in e u :
J = π 4 3 [ ∫ 0 ∞ e u − 1 u 3 d u − ∫ 0 ∞ u 3 e − u d u ]
J = π 4 3 [ ζ ( 4 ) Γ ( 4 ) − Γ ( 4 ) ]
J = π 4 3 [ 1 5 π 4 − 6 ]
J = 5 1 − π 4 1 8
Likewise:
a = 8